The popcorn book - De Paola, Tomie (New York : Scholastic, by arrangement with Holiday House, 1978)
Presents a variety of facts about popcorn and includes two recipes.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist
3.3
K-3
Keywords: Popcorn -- Juvenile literature; Popcorn; Popcorn